Root-endophytic fungi cause morphological and functional differences in Scots pine roots in contrast to ectomycorrhizal fungi - Heinonsalo, Jussi; Buee, Marc; Vaario, Lu-Min (Canadian Science Publishing, 2017)
Endophytic fungi and ectomycorrhizal fungi co-exist in the mycorrhizal root tips of boreal forest trees. However, very little is known about the functional role they play in their host's biology. The activity of enzymes responsible for important biochemical processes is used to determine the functional role of root-associated mycorrhizal fungi. However, enzyme activity is never studied in the presence of endophytic fungi in-planta. The aims of this study were to investigate the effect of Scots pine (Pinus sylvestris L.) root-isolated fungal endophytes on the host plant root morphology, to determine their functional effects using host root-excreted enzyme activity measurements, and to compare them with roots colonized by decomposer and ectomycorrhizal fungal strains and noncolonised Scots pine root tips. Our results show that endophytic fungi did not damage the pine roots in contrast to the decomposer fungi. The endophytic fungi penetrated the cortical cells of the host plant. The roots colonised by endophytic fungi produce different exo-enzymes compared with those produced by roots colonized by other fungal groups or noncolonized control root tips. Our results indicate that endophytic fungi are clearly a distinctive ecological group of fungi that have functional traits different from those of ectomycorrhizal and decomposer fungi.
Keywords: endophytic fungi; root morphology; Pinus sylvestris; mykorritsasienet; mänty; entsyymit; mycorrhizae; Pinus; enzymes